Analysis of the Influence of Financial Performance on Company Value by Disclosure of Corporate Social Responsibility and Good Corporate Governance as Moderating Variables - Muhammad Rajab (Greenation Research & Yayasan Global Resarch National, 2023)
The aim of this research is to identify the influence of financial performance to firm value with moderating variables: Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG). The main method of analysis used is the multiple linear regression. By using the manufacturing companies registered on the Indonesia Stock Exchange (IDX) during 2012-2015 as the sample with purposive sampling technique. The analysis finds that Corporate Social Responsibility and Good Corporate Governance can influence the effect of financial performance on firm value. Beside, this research also found that ROA has positive significance to Tobin's Q.